Expert System for Decision Support Division of Inheritance According to Islamic Law - Adi Fitra Andikos; Gunawan Ali; Wulan Andang Purnomo (Institute of Advanced Engineering and Science, 2016)
Develop an expert system as supporting legacy property distribution of decision which based on the Islamic law. This expert system expected can help everyone who need distribution value of legacy property by using distribution method based on the Islamic law. The legacy property value which will be distributed is legacy property after taken by the will if it was. And debt, corpse of administration cost. The distribution result is an percentage value for each heir who have right to get the property legacy after distribution process. Determination of nominal value of legacy property will not be count in this system. The user system can obtain nominal value of distribution property by multiplying the distribution percentage with whole value of legacy property. The result that taken form this expert system is output as information of heir group who has right to the legacy, and percentage value for each heir who has right to get the legacy. The inference method that used in this expert system is Forward Chaining Method. The method that used for system analysis and designing is Data Flow Oriented method by using Data Flow Diagram (DFD) tool. The database design is using Entity-Relationship Diagram (E-R Diagram) relation model.